Stand Characteristics Of Loagan Bunut Peat Swamp Forests - Jusoh, Ismail; Demise, M.; Ipor, I.B.; Tawan, C.S; Bulan, P. (Universiti Malaysia Sarawak, (UNIMAS), 2006)
The horizontal structure of the Loagan Bunut peat swamp forests ~ 5cm diameter at breast height (DBS) was studied to better understand the current status of the forest. The stand density, basal area and diameter distribution structure were assessed for all species. Forest sampling was done in three different sites representing three forest types. A total of 87 tree species was recorded from the three sites. Results show that the most common species are Shorea albida, Litsea crassi/olia, Combretocarpus rotundatus and Dactylocladus stenostachys. Other tree species that are usually found are Dyera polyphylla. Copai/era palustris and Craytoxylum glaucum. Diameter size for all species followed the reverse-J curve indicating a good overall forest regeneration. However, individual tree species such as Shorea albida did not necessarily possess the reverse-J curve, suggesting irregular regeneration. Heavy forest disturbance such as extensive logging and clearance could deplete Gonystylus bancanus trees. The peat swamp forest could naturally recover provided forest disturbances are minimal. However. concerted efforts should be made to ensure the future survival of Gonystylus bancanus in this forest. Nevertheless. long-term studies are necessary to understand the ecological trends and traits of the Loagan Bunut peat swamp forest.